Stimulation of the chemosensory TRPA1 cation channel by volatile toxic substances promotes cell survival of small cell lung cancer cells - Schäfer, Eva Anna Maria; Stohr, Stefanie; Meister, Michael; Aigner, Achim; Gudermann, Thomas; Buech, Thomas R. H. (Biochemical pharmacology, 2013)
TRPA1, a member of the transient receptor potential (TRP) family of cation channels, has mainly been characterized as a chemosensory protein in neuronal cells. TRPA1 is activated by toxic or irritating volatile agents like allyl isothiocyanate (AITC), tear gas, formalin, or cigarette smoke. To date, little is known about a function of TRPA1 in non-neuronal cells in the respiratory system and even less regarding a possible role in cancer biology. Here, we show that TRPA1 is expressed in a panel of human small cell lung cancer (SCLC) cell lines. Of note, TRPA1 mRNA was also significantly higher expressed in tumor samples of SCLC patients as compared to non-SCLC tumor samples or non-malignant lung tissue. Stimulation of SCLC cells with AITC led to a rise of the intracellular calcium concentration. This calcium response was inhibited by TRPA1 antagonists. Furthermore, AITC or formalin stimulated ERK1/2 in TRPA1-expressing HEK293 cells and in SCLC cells via a Src- and calcium-dependent mechanism. More importantly, TRPA1 activation in SCLC cells prevented apoptosis induced by serum starvation and thus promoted cell survival, an effect which could be blocked by inhibition of TRPA1 or ERK1/2. Vice versa, down-regulation of TRPA1 severely impaired anchorage-independent growth of SCLC cells. Since TRPA1 appears to play a pivotal role for cell survival in SCLC cells we propose that this channel could represent a promising target for therapeutic interventions. Furthermore, our data suggest that exogenous, inhalable activators of TRPA1 could be able to exert tumor promoting effects in SCLC cells.